Preparing Australian athletes for the Tokyo 2020 Olympics - Binnie, M. (Train smarter with science, 2019)
In this episode we chat to Dr Martyn Binnie, a physiologist assisting the coaching staff at the West Australian Institute of Sport (WAIS) for Racing Sports. Dr Binnie completed his PhD study in 2014 using sand as a training surface for team sport athletes and currently supports athletes in their training environment to troubleshoot any issues that arise, and implement changes to help the athletes take leaps in their progress.